ORGANIC MATTER LABILE FRACTIONS AND CARBON STOCKS IN A TYPIC QUARTZIPSAMMENT CULTIVATED WITH SUGARCANE HARVESTED WITHOUT BURNING - Oliveira Filho, José de Souza (2016)
The permanence of sugarcane straw on the soil surface, in systems without the pre-harvest straw burning practice, directly affects the soil organic matter dynamics. The objective of this work was to evaluate the changes in total organic carbon (TOC), carbon in the light organic matter (CLOM) and particulate organic carbon (POC), and their carbon stocks in a typic Quartzipsamment cultivated for nine years with sugarcane crops, which were conducted without the pre-harvest straw burning practice, in Paraipaba, State of Ceará, Brazil. Disturbed and undisturbed soil samples were collected at depths of 0.0-0.025, 0.025-0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.30 m, in the sugarcane crop area and in an adjacent native forest area, in order to quantify the TOC, CLOM and POC, as well as the carbon stocks accumulated in the layer 0.0-0.30 m related to these fractions (TOCSt, CLOMSt and POCSt). TOC content changes after nine years of sugarcane crops, conducted without pre-harvest straw burning, were found only in the layers 0.10-0.20 and 0.20-0.30 m. The CLOM varied only in the layer 0.025-0.05 m. The POC content changes were more noticeable than the changes in TOC and CMOL. The CLOM of the sugarcane crop area presented high similarity with TOC, which may affect their quantification in studies related to the soil organic matter dynamics. The sugarcane crop increased the TOCSt, POCSt and CLOMSt in the layer 0.0-0.30 m, compared with the adjacent native forest area.